2008
DOI: 10.3758/cabn.8.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Is task switching nothing but cue priming? Evidence from ERPs

Abstract: 74The task-switching paradigm has become an important tool for study of the cognitive control processes needed to flexibly adjust to a changing environment (for a review, see Monsell, 2003). In a typical task-switching experiment, participants have to switch between two or more tasks, and differences in response times (RTs) and accuracy between task alternations and task repetitions-that is, the so-called switch costs-are typically interpreted as a reflection of the processing demands involved in changing task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
110
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(127 citation statements)
references
References 30 publications
(61 reference statements)
15
110
2
Order By: Relevance
“…For example, a recent ERP study, which allowed an online measurement of cue-triggered processes, revealed that both switch and repetition trials elicit a P3b component (Jost, Mayr, & RosIer, 2008). These authors assumed that the P3b in the preparatory interval reflects endogenous or cognitive aspects of "context updating" (see Donchin & Coles, 1988) because the P3b amplitude was related to response speed.…”
Section: Is Preparation Switch-specific? Empirical Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent ERP study, which allowed an online measurement of cue-triggered processes, revealed that both switch and repetition trials elicit a P3b component (Jost, Mayr, & RosIer, 2008). These authors assumed that the P3b in the preparatory interval reflects endogenous or cognitive aspects of "context updating" (see Donchin & Coles, 1988) because the P3b amplitude was related to response speed.…”
Section: Is Preparation Switch-specific? Empirical Datamentioning
confidence: 99%
“…They demonstrated that the switch-related positivity occurred regardless of whether cue category repeated or switched. Jost et al (2008) directly compared ERPs in task-switch trials and cue-switch trials and found a relative negativity starting 400 ms after presentation of the target stimulus. This effect differed regarding timing and topography from the effect between cue-switch trials and cue-repetition trials, providing evidence for distinct task processing in taskswitch trials compared with cue-switch trials.…”
Section: Preparation As Interaction Of Cue Encoding and Memory Retrievalmentioning
confidence: 99%
“…Some authors have directly related this positive deflection to the P3b component as the construct of "context updating" (Donchin & Coles, 1988), which suggests that the increased positivity is assumed to reflect the endogenous control for comparison of the attributes of incoming stimuli with an internal model and the subsequent revision of the model (Barcelo, MunozCespedes, Pozo, & Rubia, 2000;Barcelo, Perianez, & Knight, 2002;Kieffaber & Hetrick, 2005). Accordingly, the late posterior positivity for switch trials has been interpreted as the advanced endogenous control processes that either update the task sets (Barcelo et al, 2002;Kieffaber & Hetrick, 2005) and/ or the stimulus-response (S-R) mapping rules (Astle, Jackson, & Swainson, 2008) in working memory or retrieve the task goals from long-term memory (Jost, Mayr, & Rosler, 2008). Furthermore, a less common finding in the ITS paradigm is the late frontal negativity 1 (LFN) for switch trials that occurs in advance of the target presentation (Astle et al, 2008;Lavric, Mizon, & Monsell, 2008;Mueller, Swainson, & Jackson, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even in this setup, reinforcement learning mechanisms could be taking place during the cuing period, since participants could adjust their correct or incorrect predictions of their previous response on the basis of repeat and switch cues, respectively. In another set of task-switching and WCST studies, cues signaling a readjustment of the task rule and cues signaling the correctness of the performance have been separated and introduced in distinct stages of the trial series (Adrover-Roig & Barceló, 2010;Jost et al, 2008;Kieffaber & Hetrick, 2005;Periañez & Barceló, 2009). In all of these studies, however, the analyses of the electrophysiological responses elicited by the feedback signals have been omitted.…”
Section: Introductionmentioning
confidence: 99%